2017
DOI: 10.1088/1361-6463/aa7715
|View full text |Cite
|
Sign up to set email alerts
|

Magnonics: spin waves connecting charges, spins and photons

Abstract: Spin waves (SW) are the excitation of the spin system in a ferromagnetic condensed matter body. They are collective excitations of the electron system and, from a quasiclassical point of view, can be understood as a coherent precession of the electrons' spins. Analogous to photons, they are also referred to as magnons indicating their quasi-particle character. The collective nature of SWs is established by the shortrange exchange interaction as well as the non-local magnetic dipolar interaction, resulting in c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 11 publications
0
26
0
Order By: Relevance
“…For continued progress, magnetic materials with specific and dedicated properties are needed, such as a high Curie temperature and an appropriate magnetic anisotropy for thermal stability [9], a high spin polarization at the Fermi energy to obtain fully spin-polarized currents, and a small magnetic damping to easily generate magnetization precession. All of these properties are desirable for STT, SOT and AOS based devices [9] but also in spin-wave-based devices, an emergent research field called magnonics [10].…”
Section: -Introductionmentioning
confidence: 99%
“…For continued progress, magnetic materials with specific and dedicated properties are needed, such as a high Curie temperature and an appropriate magnetic anisotropy for thermal stability [9], a high spin polarization at the Fermi energy to obtain fully spin-polarized currents, and a small magnetic damping to easily generate magnetization precession. All of these properties are desirable for STT, SOT and AOS based devices [9] but also in spin-wave-based devices, an emergent research field called magnonics [10].…”
Section: -Introductionmentioning
confidence: 99%
“…Emerging applications in magnonics [1], spin-orbitronics [2] as well as fundamental studies in linear and non-linear magnetization dynamics [3] rely on materials that exhibit low values of the magnetic damping parameter. Insulating ferromagnets and ferrites -lacking a significant electronmagnon relaxation channel -have historically exhibited the lowest magnetic dissipation at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, two recent studies reported the growth of Co25Fe75 on MgO and MAO resulting in values of the damping parameters around 0.001 [11,12]. Removing the constraint of epitaxial growth on single crystalline substrates while maintaining low magnetic damping and high film uniformity may enable integration of this material in a wide range of spintronic and magnonic devices [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Magnonics, a young and evolving field, has received extensive research interests in the modern magnetism research community [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Similar to spintronics, which deals with electron spin, magnonics utilizes magnon (the quanta of spin wave) to carry and process information.…”
Section: Introductionmentioning
confidence: 99%